Incidence of Hyponatremia During a Continuous 246-km Ultramarathon Running Race - Seal, Adam D.; Anastasiou, Costas A.; Skenderi, Katerina P.; Echegaray, Marcos; Yiannakouris, Nikos; Tsekouras, Yiannis E.; Matalas, Antonia L.; Yannakoulia, Mary; Pechlivani, Fani; Kavouras, Stavros A. (Frontiers in Nutrition, 2019)
Purpose: The purpose of this observational study was to examine the incidence of exercise-associated hyponatremia (EAH) in a 246-km continuous ultra-marathon. Methods: Over two years, 63 male finishers of the annual Spartathlon ultra-marathon foot race from Athens to Sparta, Greece were included in the data analysis. A blood sample was drawn from an antecubital vein the day before the race as well as within 15 min post-race and analyzed for sodium concentration. During the second year of data collection, blood was also drawn at the 93-km checkpoint (n = 29). Height and weight were measured pre and post-race. Results: Mean race time of all subjects was 333 hours with a range of 23.5 hours and 36.0 hours. Of the 63 finishers recruited, nine began the race with values indicative of mild hyponatremia. Seven runners were classified as hyponatremic at the 93-km checkpoint, three of whom had sodium levels of severe hyponatremia. After the race, 41 total finishers (65%) developed either mild (n = 27, 43%) or severe hyponatremia (n=14, 22%). Mean change in bodyweight percentage and serum sodium from pre-race to post-race was -3.62.7% (-2.51.9 kg) and -6.65.6 mmol∙L-1, respectively. Pre-race serum sodium level was not a significant predictor of post-race serum sodium levels (= 0.08, R2 = 0.07, P = 0.698), however, there was a significant negative association between change in bodyweight percentage and post-race serum sodium concentration (= -0.79, R2 = 0.29, P = 0.011). Conclusion: The incidence of EAH of 52% and 65%, when excluding or including these individuals with pre-race hyponatremia, was the highest reported in current literature.